Can we expand the indications for laparoscopic liver resection? A systematic review and meta‐analysis of laparoscopic liver resection for patients with hepatocellular carcinoma and chronic liver disease. (7th February 2015) - Morise, Zenichi; Ciria, Ruben; Cherqui, Daniel; Chen, Kuo‐Hsin; Belli, Giulio; Wakabayashi, Go
Abstract: Liver resection (LR) for patients with hepatocellular carcinoma (HCC) and chronic liver disease (CLD) poses a high risk of serious postoperative complications and multicentric metachronous lesions requiring repeated treatment. The efficacy of laparoscopic LR (LLR) for such patients has yet to be established. The objective of this study is to test the outcomes of LLR for HCC with the aim of considering potential expansion of the indications for LLR. We performed a systematic review of the pertinent English‐language literature. Our search yielded four meta‐analyses and 23 comparative studies of LLR for HCC. On the basis of the findings from these studies and our newly conducted meta‐analysis, the possibility for expanding the indications for LLR to HCC was examined. The studies show that LLR (vs open) for HCC generally yields better short‐term outcomes without compromising long‐term outcomes, and that incidences of postoperative ascites and liver failure are decreased with LLR. Several studies show the benefits of LLR for patients with severe CLD and for repeat surgery. Reductions of postoperative ascites and liver failure are among the advantages of LLR. These characteristics of LLR may allow us to expand the indications of LLR to HCC with CLD. © Japanese Society of